Characterization of the infection cycle of Phytophthora betacei during disease development on tree tomato (Solanum betaceum) (2017)
"Phytophthora betacei is a recently described oomycete plant pathogen closely related to P.infestans sensu stricto. This plant pathogen infects tree tomato (Solanum betaceum) crops, but is not able to infect potatoes or tomatoes, the main hosts of P. infestans. The aim of this study was to characterize the infection cycle of P. betacei using microscopy and molecular approaches. To this end, susceptible tree tomato plants were inoculated with a sporangial solution from several strains, and the progression of the disease was monitored based on six epidemiological parameters. The results indicated that strains from P. betacei display a highly variable disease phenotype. To understand the infection cycle at the cell and molecular level, one highly aggressive strain was selected, and inoculation assays were performed. Samples collected from the inoculated plants 3, 6, 9, 12, 24 24, 48, 72, and 96 hpi were visualized using Scanning Electron Microscopy (SEM) and light Microscopy (trypan blue staining). Timing and progression of the disease was further validated with qRT-PCR by assessing the expression levels of infection-stage specific markers such as haustorium-specific membrane protein hmp1 and the cell cycle regulator Cdc14 along the infection cycle. Results indicated that the infection cycle of P. betacei differs from that of P. infestans in that the infection cycle of the former is characterized by a longer biotrophic stage, greater lesions and greater sporulation capacity when evaluated on the same host. Varying levels of expression were detected for both genes along the infection cycle, and their profile was consistent with the results observed on the whole plant inoculations. This study provides novel insights into the interaction between P. betacei and S. betaceum and provides a reference transcriptome of the two organisms."--Tomado del Formato de Documento de Grado.